Analysis of Prospective Teacher Students Errors in Making Math Test Instruments Based on Bloom's Taxonomy Revised - Adhitya, Yusuf (Eduscape : Journal of Education Insight, 2024)
This study aims to describe the errors of prospective teacher students in making math test instruments based on cognitive levels from the Bloom’s Taxonomy Revised (BTR). BTR consists of LOTS (C1-C3) and HOTS (C4-C6) levels. This research included descriptive qualitative research. The subjects of this study were 19 prospective teacher students, namely the mathematics education department in the Mathematics Learning Evaluation course. Based on the results of the study, it was obtained that prospective teacher students made mistakes at both levels but more at the HOTS level. At the LOTS level, it is on the error level C3; at the HOTS level, it is spread at all levels, namely C4-C6. An indication of error that often arises is that prospective teacher students cannot compile questions according to their level of cognition. The questions made are often still below the level they should be. The level of the questions made is still below the level that it should be.